Tools for entertainment or learning? Exploring students’ and tutors’ domestication of mobile devices - Bober, Magdalena; Hynes, Deirdre; Lau, Anshul (Proceedings of the International Conference on Networked Learning, 2016)
This paper presents findings from a research project at a school of humanities, languages and social science at a UK university that investigated staff and student attitudes towards and uses of mobile devices (smartphones, tablets and laptops). The study had a dual focus on personal and university-related uses. It applied the domestication of technology approach (Silverstone & Hirsch, 1992) to understand how mobile devices have been appropriated by users in their everyday lives, how they have become part of daily routines and spatial arrangements and what rules are being negotiated around their use. Data in the present study was collected via in-depth interviews with 18 teaching staff and six focus groups with a total of 19 students across different departments in the school. This paper presents findings on device acquisition and ownership, device use and associated meanings, as well as situating devices within daily routines and spaces. In each section, results from the staff and student data are compared. The research identified distinct uses of different devices in terms of university-related and personal uses but also areas of overlapping use. Furthermore, students and tutors associated important symbolic meanings with their devices, had incorporated them into daily routines and spatial arrangements in new ways and attempted to self-regulate use in different situations. While tutors were starting to make use of mobile devices in their teaching practice in innovative and meaningful ways, students had a less well defined understanding of the educational benefits of mobile devices. Institutional policy also played a role in shaping students’ and tutors’ use. Not many empirical studies exist that explore the link between educational and personal, everyday use of mobile devices. It is in this area that this research aims to make a contribution to knowledge. The findings are also of importance to practitioners and educational institutions planning to implement mobile device-based learning.